Analysis of Interface & Information Content of LIPI Botanical Gardens Website Based on Scanmic Model - Dwi Putra, Kadek Aryana; Nashihuddin, Wahid; Hidayatullah, Fauzan (Record and Library Journal, 2021)
Background of the study: Website is an online media institution to promote and disseminate the information services to the public. The LIPI botanical garden website has interesting information to study, such as information of plant collections, library services, and website content. The Scanmic model can be used to analyze the appearance and information content of the botanical garden website. Purposes: to know the plant collections, library services, and website analysis results at LIPI botanical gardens, namely KR Bogor, KR Cibodas, KR Purwodadi, and KR Eka Karya Bali. Method: This type of research is descriptive – qualitative, data sources by: information retrieval on the LIPI botanical garden website, literature study, and documentation. Analysis of the website appearance and content by Scanmic model criteria, namely: screen design, content, accessibility, navigation, media use, interactivity, and consistency. Findings: The results of this study indicate that the plant collection in each botanical garden is different, and the information can be accessed through library services. The results of the Scanmic model analysis showed that of the 7 criterias of 21 indicators only 15 indicators were fulfill by the LIPI botanical garden website. Conclusion: It is necessary to develop the features and content of the LIPI botanical garden website continuosly to be more user friendly and interactive.